A Multi-source Localization System for Driverless Material Transport in Mixed Indoor and Outdoor Areas - Herbert, Meike; Zwingel, Maximilian; Czapka, Christian; Franke, Jörg (Production at the Leading Edge of Technology, 2021)
To ensure material supply in production, the focus of research and development is on flexible, automated intralogistics solutions. The automation of material transport in mixed indoor and outdoor environments enabling transport processes between factory buildings is still challenging. The seamless localization of transport vehicles with the required accuracy is a core issue for navigation. While global navigation satellite systems can be used outdoors, other approaches like wireless networks or light detection and ranging technology are applied indoors. Additional sensors e.g. incremental encoders or inertial measurement units are used to create a multi-source localization system, which can adapt to the ideal mix of sensor sources, especially in transition areas. In this paper, a localization approach for driverless transport vehicles is presented in detail including applied methods for data fusion and implementation. The localization approach is validated using a tow truck equipped with sensors for autonomous transport.
Keywords: Intralogistics; Autonomous material transport; Localization